Nurse-Doctor Interprofessional Collaboration In Hospital: Study Description - Wirda Y Dulahu; Dewi Suryaningsi Hiola; Cindy Puspita Sari Haji Jafar; Andi Mursyidah; Sitti Fatimah M. Arsad; Rozianti H Biya; Saskia Praditya (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Interprofessional collaboration is a partnership between professions who have different educational backgrounds and work together to solve patient health problems and provide needed health services. Interprofessional collaboration carried out by various health care professionals is an efficient and effective strategy in improving service quality. Interprofessional collaboration is also needed to increase satisfaction and create good quality health services. The method in this study is a quantitative descriptive survey. Data collection by interview method, measurement by NPCS (nurse-physicians collaboration scale). The sample of this research are nurses and doctors in RSUD Toto Kabila. This activity was carried out by 3 lecturers and 1 partner for about 4 months. Nurse-doctor interprofessional collaboration according to the perception of nurses at the Toto Kabila General Hospital, the results obtained from 129 nurses, a total of 117 (90.3%) nurses rated the doctor's collaborative behavior in the good category and a number of 12 (9.3%) nurses rated the doctor's collaborative behavior in the moderate category. Interprofessional collaboration nurse-doctor according to the perception of doctors at Toto Kabila Hospital showed that most of the respondents, namely 11 (84.6%) respondents considered nurses to carry out interprofessional collaboration well and as many as 2 (15.4%) respondents considered the interprofessional collaboration of nurses sufficient. The results showed that Interprofessional Collaboration between nurses and doctors mostly showed good results but there were still some that were still lacking in implementation so that it was necessary to increase interprofessional collaboration for all aspects of service in hospitals because with good collaboration it will create good quality health services.